Incremental Value of Sestamibi SPECT/CT Over Dual-Phase Planar Scintigraphy in Patients With Primary Hyperparathyroidism and Inconclusive Ultrasound - Assante, Roberta; Zampella, Emilia; Nicolai, Emanuele; Acampa, Wanda; Vergara, Emilia; Nappi, Carmela; Gaudieri, Valeria; Fiumara, Giovanni; Klain, Michele; Petretta, Mario; Cuocolo, Alberto (Frontiers in Medicine, 2019)
Background: We evaluated the incremental value of [99mTc]sestamibi single photon-emission computed tomography (SPECT)/computed tomography (CT) over planar imaging for localization of abnormal parathyroid tissue in patients with primary hyperparathyroidism. Methods: Forty-six patients with biochemical evidence of hyperparathyroidism and inconclusive ultrasound underwent sestamibi dual-phase planar scintigraphy and SPECT/CT for preoperative localization of parathyroid adenoma. Imaging findings were compared with histopathological data. Decision tree analysis was performed to evaluate the value of SPECT/CT over planar scintigraphy for classifying patients with or without hyperfunctioning parathyroid tissue. The added value of SPECT/CT was also evaluated by decision curve analysis. Results: Planar scintigraphy was positive for presence of hyperfunctioning parathyroid in 52% of patients, with sensitivity of 63% and specificity of 100%. SPECT/CT was positive in 80% of patients with sensitivity of 97% and specificity of 100%. At decision tree analysis, after an initial split on planar imaging results, no further split was performed in patients with positive results, while those with negative results were further stratified by SPECT/CT. At decision curve analysis, the model including SPECT/CT was associated with the highest net benefit compared to the model including only planar technique and to a strategy considering that all patients should be treated. Conclusion: Sestamibi SPECT/CT provides incremental value over dual-phase scintigraphy in preoperative localization of hyperfunctioning parathyroid tissue in subjects with inconclusive ultrasound. Hybrid technique allows a better identification of pathological lesion to perform minimally invasive surgery and showed the highest net benefit, improving selection of surgical approach.